Functionaries’ ‘duty to act’: - Nicholus Tumelo Mollo (Perspectives in Education, 2024)
The safety of teachers has been researched in South Africa, but less is known about education law that regulates functionaries’ duty to act to ensure teachers’ right to safety from violence in public schools. Section 12(1)(c) of the Constitution of 1996 provides that “(1) [e]veryone has the right to freedom and security of the person, which includes the right ... (c) to be free from all forms of violence from either public or private sources” (RSA, 1996a). This study focused on teachers’ right to safety from violence when they are on duty in public schools. The study aimed to identify and discuss various South African laws that regulate the duty to act to protect teachers’ right to safety from violence in public schools and to investigate how these laws are applied in practice by asking three research questions. The study employed a qualitative research approach grounded in an interpretive paradigm, underpinned by a theory of social safety that recognises the importance of teachers feeling secure in their interactions with others. Qualitative data were collected employing document analysis of education law and previous empirical studies (secondary data from 2013 to 2023). The findings revealed that there is sufficient provision of education law in South Africa that regulates functionaries’ duty to act to protect teachers’ right to safety from violence in public schools. However, the challenge lies in the insufficient understanding and implementation of the provisions outlined in education laws. It is recommended that functionaries be trained on the duty to act to protect teachers’ right to safety from violence. The attainment of teachers’ safety from violence hinges on the understanding and application of the existing provisions within education law that governs the duty to act.